Selective parathyroid autotransplantation prevent permanent hypoparathyroidism after total thyroidectomy with central neck dissection - Sun, Haili; Gao, Li; Xiao, Guizhou; Xie, Lei; Zhuang, Yiyu; Wang, Jianbiao (Frontiers in Surgery, 2025)
BackgroundThe impact of parathyroid gland autotransplantation on permanent hypoparathyroidism remains incompletely understood. This study aimed to ascertain how selective autotransplantation of parathyroid glands affects the occurrence of permanent hypoparathyroidism after total thyroidectomy with central neck dissection (CND).MethodA retrospective cohort study encompassed consecutive patients with papillary thyroid carcinoma who underwent primary total thyroidectomy plus CND from January 2008 to December 2010 and January 2012 to December 2019. Patients were categorized into two groups (0 and ≥1 parathyroid glands autotransplanted, respectively).ResultThe autotransplantation group comprised 501 patients, while the non-autotransplantation group comprised 652 patients. The autotransplantation group showed significantly lower permanent hypoparathyroidism than the non-autotransplantation group [1.2% (6 of 501) vs. 4.4% (29 of 652), P = 0.001]. Out of the total 1,153 patients, 652 (56.5%) had no autotransplanted glands, and 358 (31.0%), 136 (11.8%), and 7 (0.6%) had 1, 2, and 3 glands autotransplanted, respectively. As the number of autotransplanted glands increased (from 0 to 3), the prevalence of permanent hypoparathyroidism was 4.4% (29 of 652), 1.4% (5 of 358), 0.7% (1 of 136), and 0.0% (0 of 7), respectively (P = 0.016). Multivariate logistic analysis revealed that parathyroid autotransplantation independently prevented postoperative permanent hypoparathyroidism.ConclusionSelective parathyroid autotransplantation is associated with a lower risk of permanent postoperative hypoparathyroidism. Autotransplantation is recommended for parathyroid glands that are devascularized or challenging to preserve in their original location.